Monitoring & Remote Operation of an Engine Test Cell - Turner, Jamie (My University, 2014)
In the automotive industry engines are regularly tested and evaluated by running them for a prolonged time under controlled conditions; environmental conditions, engine load, and drive cycle. These tests are performed in an engine test cell; a computer controlled environment with mechanical fittings and sensors to facilitate the testing of an engine. Our goal was to develop a software suite that provides a distributed graphical interface to the data acquisition and control systems of an engine cell. As we found existing systems to be inadequate in providing a distributed interface, we designed and developed a light weight flexible software suite to remotely, over a network, observe and control the parameters in an engine cell. We used the Fast Light Toolkit (FLTK) GUI library, with networking sockets and process threads to establish the software architecture of the engine test system. Through use of process threads, the client architecture divides tasks into network data sending and receiving, local channel synchronization, and interface operation. Networking sockets used in network data sending and receiving facilitate synchronization of each clients' channel storage and host's channel data. The FLTK GUI library produces visual interactive components of the interface for invoking interactions. Distributed interfacing allows display and modification of the engine cell's operation remotely in locations where relocating an engine cell is not feasible. These locations, such as demonstrations to distant clients and meeting rooms, display the current status of the engine cell through its interfaces without requiring migration of the engine cell to the specified rooms.
Keywords: Engine Test Cell; FLTK; Data Acquisition and Control; Automotive Testing; Remote Operation